2014
DOI: 10.1016/j.ndteint.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Accurate depth measurement of small surface-breaking cracks using an ultrasonic array post-processing technique

Abstract: a b s t r a c tIn this paper, the half-skip configuration of the Total Focusing Method (TFM) is used to image and size surface-breaking cracks. The TFM is an ultrasonic array post-processing technique which is used to synthetically focus at every image point in a target region. This paper considers the case of inspecting for cracks which have initiated from the far surface of a parallel-sided sample using an array on the near surface. Typically, only direct ray paths between the array and image points are incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 16 publications
2
56
0
2
Order By: Relevance
“…For the TFM images, with the smaller crack depth, the indication of the crack tip is closer to the indication of the crack root, as the energy of the tip diffraction is much weaker than the energy reflected by the root corner, the indication of the crack tip is much weaker than the root, which causes the tip to be masked by the root in the TFM image of the 1λ deep crack. The smallest crack that TFM can successfully reconstruct is about 2λ, which shows good consistency with other research focused on imaging small cracks [12]. The TFM algorithm shows excellent robustness to noise as the addition of the noise does not affect the TFM images.…”
Section: Cracksupporting
confidence: 80%
See 3 more Smart Citations
“…For the TFM images, with the smaller crack depth, the indication of the crack tip is closer to the indication of the crack root, as the energy of the tip diffraction is much weaker than the energy reflected by the root corner, the indication of the crack tip is much weaker than the root, which causes the tip to be masked by the root in the TFM image of the 1λ deep crack. The smallest crack that TFM can successfully reconstruct is about 2λ, which shows good consistency with other research focused on imaging small cracks [12]. The TFM algorithm shows excellent robustness to noise as the addition of the noise does not affect the TFM images.…”
Section: Cracksupporting
confidence: 80%
“…The backwall of the object can be regarded as a strong reflector that would bring a strong specular reflection. Conventionally, this problem is solved by detecting the crack at an oblique incident angle (for example θ test = 45 • ), the resulting measured signals will only contain the tip diffraction and the echoes from the root corner since the specular backwall reflection will not be measured by the array [12]. However, with longer propagation distance there will be greater attenuation, reducing signal-to-noise, and similarly coherent noise from grain scattering will also be worse for longer path lengths.…”
Section: A Imaging For Surface-breaking Cracksmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, researchers have come up with solutions. Felice et al [8] used ultrasonic-array total focusing technology to measure the depth of surface cracks (<1 mm). Hu et al [9] reported a stereoscopic fluorescence profilometry to measure the thickness and morphology of transparent films.…”
Section: Introductionmentioning
confidence: 99%